Salivary Antioxidant Profile in Patients with Systemic Sclerosis and Periodontitis - Stefan I. Sredojevic; Slavica Pavlov Dolijanovic; Ivan Dozic; Jovana Kuzmanovic Pficer; Zoran Aleksic; Natasa S. Nikolic-Jakoba (Mediators of Inflammation)
Objective. The aim of the present study was to compare periodontal status and antioxidant profile in unstimulated saliva of systemic sclerosis (SSc) patients with periodontitis and systemically healthy periodontitis patients. Design. Twenty patients with established diagnoses of systemic sclerosis and periodontitis (SSc group) and 20 systemically healthy individuals with periodontitis (P group) were enrolled in the study. Clinical periodontal parameters (clinical attachment level (CAL), gingival recession (GR), periodontal probing depth (PPD), and gingival index (GI)) and concentration of uric acid (UA), superoxide dismutase (SOD), and glutathione peroxidase (GPX) in unstimulated saliva samples were assessed. Results. There were significantly higher mean values of CAL (4.8±0.21 mm versus 3.18±0.17 mm; p≤0.001) and GR (1.66±0.90 mm versus 0.46±0.54 mm; p≤0.001) in the SSc group when compared to the P group. Significantly higher level of GPX (p≤0.001) and SOD (p≤0.001) in unstimulated saliva was detected in the SSc group in comparison with the P group. The specific activity of UA did not significantly differ between the two groups (p=0.083). Conclusion. The results may indicate higher periodontal destruction and antioxidant perturbations in unstimulated saliva of SSc patients with periodontitis compared to systemically healthy periodontitis patients.